Healthy Life Education for Students In Malaysia - Mujiarto; Miftahul Falah; Budi Hendrawan; Gilang Sepriangga Nuryudi; Desta Hikmah Ramdani; Joan Sepni Subagja; Reza Hawari; Adam Firdaus; Slamet Rebiyanto; Anggia Suci Pratiwi; Milah Nurkamilah; Rissa Nuryuniarti; Aceng Sambas; Neni Nuraeni; Gugun Gundara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Healthy living behavior is a reflection of a family lifestyle that always pays attention to and maintains the health of all family members. School-age children are a critical age group because at that age a child is vulnerable to health problems. In addition, school-age children are also in a condition that is very sensitive to stimuli so they are easy to guide, direct, and still have good habits, including healthy living habits. Children of this age also have the trait of always wanting to convey what they receive and know from other people. The results of observations made at the Kuala Langat Malaysia Guidance Centre still have a lack of healthy behavior. The conditions of the students were very diverse and the facilities were inadequate, because all classes, from grade 1 to grade 6, were made into 1 class. Washing hands with soap (Hand Hygiene) is one of the healthy living behavior in students. This is important for children who are vulnerable to both communicable and non-communicable diseases. The method of implementing community service is through education and the practice of washing hands with soap directly to students. The results show that students and teachers are very enthusiastic and follow every step practiced by the presenters. they were happy and practiced together after the activity was over. By providing education on healthy living, especially hand washing, it is hoped that teachers and students at the Kuala Langat Guidance Centre will have good and healthy habits.